Kesiapan Sumber Daya Manusia Menghadapi Artificial Intelligence: Studi Pustaka: Penelitian - Marssel Michael Sengkey; Ni Kadek Diah Shinta Kartika; Gloria Natalie Lantu; Hestria Br Ginting; Giva Syaloom Sembor (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2025)
The development of Artificial Intelligence (AI) over the past ten years has significantly changed the way companies manage their workforce, from orientation and training to skill development and performance appraisal systems. These changes not only impact work transformation methods but also force individuals to adapt comprehensively to increasingly intelligent, flexible, and autonomous technology. This research method uses a literature review that compiles and analyzes various studies related to HR readiness to face the penetration of AI in the modern workplace. The results of this study identify four main aspects of human resource readiness: digital literacy, psychological and behavioral readiness, organizational readiness, and AI ethics and governance readiness. These findings confirm that strengthening these four aspects is a crucial prerequisite for organizations to ensure effective and sustainable AI implementation that can improve performance and competitiveness in the era of digital transformation.